# True or false 12+ 5 – 3 = 12 + (5 – 3)

Answers: 1

## Answers

True or false 12+ 5 – 3 = 12 + (5 – 3)...

Answers: 1

True or false 12+ 5 – 3 = 12 + (5 – 3)...

the answer is true

12 + 5 - 3 = 12 + (5 - 3)

17 - 3 = 12 + 2

14 = 14

False

Step-by-step explanation:

it is. true

Step-by-step explanation:

17-3=12+2

14 to 14

true

Step-by-step explanation:

12 + 5 - 3 = 12 + (5 - 3)

17 - 3 = 12 + 2

14 = 14

True

Step-by-step explanation:

Following PEMDAS priority, (Parenthesis, Exponent, Multiplication, Division, Addition, Subtraction)

14 = 14

true

Step-by-step explanation:

PEMDAS rule.

Step-by-step explanation:

When solving, always remember the acronym PEMDAS (Parenthesis, Exponent, Multiplication, Division, Addition, and Subtraction)

12 + 5 – 3 = 12 + (5 – 3)

12 + 5 – 3 = 12 + (5 – 3)

17 – 3 = 12 + (2)

14 = 12 + 2

14 = 14

#answerForTrees